Fertilizer responsiveness of high-yielding drought-tolerant rice in rainfed lowlands - Banayo, Niño P. M.; Rahon, Raymond E.; Sta. Cruz, Pompe; Kato, Yoichiro (Informa UK Limited, 2021)
Recent advances in rice breeding in tropical Asia led to the release of high-yielding drought-tolerant cultivars. Together with the use of these cultivars, improved nutrient management under drought should further increase rice productivity in rainfed lowland ecosystems. The objectives of this study were to evaluate cultivar differences in the responses of plant growth and grain yield to fertilizer application regimes. We compared 13 drought-tolerant rice cultivars with two irrigated rice cultivars under three nutrient management conditions in irrigated and rainfed lowlands in the Philippines during the wet seasons of 2014 and 2015. Drought stress was mild in both years, with a yield reduction of 11% to 12%, and there was no significant cultivar × nutrient management interaction in yield. The drought-tolerant cultivar NSIC Rc282 proved fertilizer-responsive, and had similar yield to those of the popular high-yielding cultivar NSIC Rc222 under all conditions. An ancillary experiment in 2016 confirmed that NSIC Rc282 was more drought-adapted than NSIC Rc222, with 11% to 37% higher yield under stress. In order to maximize the yield, NSIC Rc282 required N application only when the drought ended, whereas NSIC Rc222 required additional N during the drought. This shows that the details of drought-adaptive nutrient management differ between irrigated and drought-tolerant rice cultivars. We suggest that the introduction of high-yielding drought-tolerant rice cultivars will both improve productivity and increase the nutrient-use efficiency of agriculture in rainfed environments